Compression neuropathy of the suprascapular nerve in tennis players - Scheider, C.; Krahl, H.; Pieper, H. G. (1997)
Functional impairment of the suprascapular nerve is common among volleyball players. Researchers of the Orthopaedic Clinic at the Alfred Krupp Hospital in Essen-Rüttenscheid, Germany reported on a clinical study conducted to determine the incidence of the syndrome among tennis players. The latency time of the suprascapular nerve was measured in both shoulders in a total of 116 junior and senior tennis players, and in 20 non-tennis players in both age groups. None of the tennis players studied had any pathological suprascapular neuropathy, although the latency time was higher in the dominant shoulder, and increased with age. The researchers concluded that the most likely explanation for the high incidence of suprascapular neuropathy in volleyball players lies in the complex motion involved in catching the ball. This cannot be compared to any stroke in tennis, and there appears to be no tennis-specific damage of the suprascapular nerve.